2019
DOI: 10.1111/1475-4932.12472
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Gender Gap in Financial Literacy: Evidence from Australia

Abstract: Using micro‐data from the Household, Income and Labour Dynamics in Australia Survey, and the Oaxaca–Blinder decomposition technique, this paper examines the determinants of the gender gap in financial literacy. The analysis suggests that human capital variables, such as age and education, are not important in explaining the gender gap in financial literacy. Labour market variables, such as sector, occupation, industry, union membership and labour market status, are important and explain around 16 per cent of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 54 publications
1
62
0
4
Order By: Relevance
“…We note that in previous studies, it has been important to consider the direction of the causal relationships between observed financial literacy and selected independent variables such as occupation. As Preston and Wright (2019) note, it may be that occupation experience increases financial knowledge or instead that financial literacy shapes occupational choice. In the case of personality traits, there is no theoretical reason to expect that greater financial knowledge might alter traits of “openness” or “neuroticism.”…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We note that in previous studies, it has been important to consider the direction of the causal relationships between observed financial literacy and selected independent variables such as occupation. As Preston and Wright (2019) note, it may be that occupation experience increases financial knowledge or instead that financial literacy shapes occupational choice. In the case of personality traits, there is no theoretical reason to expect that greater financial knowledge might alter traits of “openness” or “neuroticism.”…”
Section: Discussionmentioning
confidence: 99%
“…As a share of the gross differential in financial literacy and financial capability, endowments account for between 16 and 89% of the gap between men and women when the models include psychological variables (Panel B at Table 7). More specifically, our results (at Panel B of Table 7) find that more than half (0.31 on 0.58) of the gross differential in financial literacy scores between men and women is explained by underlying differences in sociodemographic and psychological characteristics, a share that is substantially higher than previous studies using the same decomposition technique but different sets of explanatory variables (Fonseca et al ., 2012; Cupák et al ., 2018; Preston and Wright, 2019). On the other hand, nearly half of the gender gap in financial literacy scores remains unexplained, with very large effects of the coefficients, moderated by the interaction effect (0.40 and −‐0.14, or 0.26 on 0.58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the young boys were better in coping with risks and with regards to financial knowledge compared to young women while the latter were more concerned in money management and spending. Preston and Wright (2019) studied the relation between financial literacy and gender in Australia. In their study, they used the variables including age and education and found that these variables were insignificant to explain the gender difference.…”
Section: Literature Studymentioning
confidence: 99%